PRLR, MC4R AND LEP POLYMORPHISMS, AND ADIPOQ, A-FABP AND LEP EXPRESSION IN CROSSBRED MANGALICA PIGS - Tempfli; Károly; Simon; Zoltán; Kovács; Bálint; Posgay; Miklós; Bali Papp; Ágnes (Journal of Animal and Plant Sciences, 2015)
Mangalica×Duroc crossbred pigs were genotyped for the G1789A prolactin receptor (PRLR), G1426A melanocortin-4 receptor (MC4R), and T3469C leptin (LEP) single nucleotide polymorphisms (SNPs) by means of the PCR-RFLP method; genotype-trait associations were also analysed. The PRLR genotype did not influence (P>0.05) any production traits monitored, whereas the MC4R genotype significantly (P<0.05) affected backfat thickness and average daily gain during the fattening period. The LEP genotype was also significantly (P<0.05) associated with average daily gain. In crossbred gilts the expression of the adiponectin (ADIPOQ), adipocyte fatty acid-binding protein (A-FABP), and LEP genes was analysed in adipose and muscle tissues using qRT-PCR. ADIPOQ was predominantly expressed in backfat (P<0.05); however, mRNA was also detected in muscle samples indicating high intramuscular fat content. The A-FABP and LEP genes were more active in fat tissue with moderately lower levels also in muscle, contributing to intramuscular fat accumulation. MC4R and LEP polymorphisms are promising markers for production traits in the crossbred animals, whereas ADIPOQ expression is suggested as a potential indicator of elevated intramuscular fat content.
Keywords: gene expression; polymorphism; backfat thickness; Mangalica pig